Microalgal-bacterial flocs and extracellular polymeric substances for optimum function of integrated algal pond systems - Jimoh, Taobat Adekilekun (Rhodes University, Faculty of Science, Institute for Environmental Biotechnology)
Despite the dire state of sanitation infrastructures, water scarcity, and the dwindling reserve of natural resources due to ever-increasing population growth, implementation of a suitable technology that can provide a solution to all these issues continues to be ignored. The integrated algal pond system (IAPS) is a wastewater treatment technology that combines the processes of anaerobic digestion and photosynthetic oxygenation to achieve wastewater treatment and facilitate the recovery of treated water and resources in the form of biogas and microalgal-bacterial biomass. The natural process of bioflocculation through microalgal-bacterial mutualism and production of extracellular polymeric substances (EPS) in high rate algal oxidation ponds (HRAOPs) of an IAPS increases efficiency of wastewater treatment and potentially enhances harvestability and biomass recovery, which could contribute significantly to the successful establishment of a biorefinery. Using a 500 PE pilot-scale IAPS supplied domestic sewage coupled with laboratory experiments, this study investigated the importance and function of in situ EPS production and MaB-floc formation in HRAOP. A metagenomic study revealed the biological components of the biomass or mixed liquor suspended solids (MLSS) produced in HRAOP and showed that the suspended biomass is composed largely of eukaryotes that were dominated by the colonial microalgae Pseudopediastrum sp. and Desmodesmus sp., and a diverse range of prokaryotes including bacteria and cyanobacteria. Dominance, within the bacterial population, by a sulphur-oxidizing bacterium, Thiothrix which comprised up to 80% of the prokaryotes, coincided with a period of poor flocculation and was therefore rationalized to have contributed to bulking and poor biomass settleability. Otherwise, good flocs were formed in the MLSS with settleability up to 95% and, within 1 h. The formation of MaB-flocs appeared to be dependent on EPS concentration of the mixed liquor due to the observed positive correlation between soluble EPS (S-EPS), biomass concentration, and settleability. The contribution and role of MLSS components towards the formation and sustenance of MaB-flocs were further demonstrated in laboratory experiments using pure strains of microalgae, cyanobacteria, and bacteria. Results showed that pure cultures of dominant microalgae in MLSS, Pseudopediastrum sp. and Desmodesmus sp. achieved a rapid 92 and 75% settleability within 3 h. A self-flocculating filamentous cyanobacterium, Leptolyngbya strain ECCN 20BG was isolated, characterized, and shown to achieve 99% settleability within 5 min by forming large tightly aggregated flocs. In further experiments, this strain was found to improve the settleability of MLSS by an average of 20%. Bacterial strains identified as Bacillus strain ECCN 40b, Bacillus strain ECCN 41b, Planococcus strain ECCN 45b, and Exiguobacterium strain ECCN 46b were also observed to produce sticky EPS-like materials in pure cultures that could also contribute to the aggregation of cells in a mixed environment. Given these results, various factors and/or mechanisms that might enhance microbial aggregation and biomass recovery from HRAOP MLSS were identified in this study and include; (1) dominance by larger colonial microalgae prevents disintegration of MaB-flocs and enhances recovery of biomass from MLSS by gravity sedimentation, (2) presence of filamentous cyanobacteria species that can self-flocculate to form an interwoven network of filaments may play an important role in the structural stability and settleability of MaB-flocs in MLSS, and (3) production of EPS to form the matrix or scaffold whereon all microbial components aggregate to develop a microenvironment. Indeed, all forms of EPS, except for that produced by Bacillus strain ECCN 41b, showed bioflocculating property and were able to serve as flocculants for the recovery of Chlorella, an alga known for its poor settleability. A combination of biochemical analyses and FTIR spectroscopy revealed the importance of carbohydrate enrichment of these biopolymers. Carbohydrate concentration in all forms of EPS was between 12 and 41% suggesting that production of these compounds by microbes within the MLSS contributed to MaB-floc formation. EPS extracted from bulk MLSS and EPS produced by Bacillus strains possessed some surface-active properties that were comparable to Triton X-100, indicating potential application in bioremediation and recovery of oil from contaminated soil and water. In particular, EPS generated from Bacillus strain ECCN 41b displayed relatively distinct properties including the quantity produced (> 500 mg/L), increased viscosity, inability to flocculate microalgal cells, a rhamnolipid content of 32%, and a higher surface-activity. Based on these results, Bacillus strain ECCN 41b was rationalized to produce anionic EPS with potential application in metal or oil recovery. In addition to EPS production, the bacteria Planococcus strain ECCN 45b and Exiguobacterium strain ECCN 46b appeared pigmented. Based on partial characterization using UV/Vis spectrophotometry, thin-layer chromatography, FTIR, and NMR, the pigments produced by these two strains appeared to be identical and were tentatively identified as ketocarotenoids. This study successfully demonstrated the importance of EPS production and formation of MaB-flocs in the MLSS from HRAOP of an IAPS treating domestic sewage. It is evident that increased settleability of the biomass does contribute to the reported efficiency of wastewater treatment by IAPS and would reduce both total suspended solids (TSS) and chemical oxygen demand (COD). In addition, demonstration that this biomass contains products of value such as carotenoids and EPS with potential for commercial use strengthens the idea of using IAPS as a platform technology for innovation of the wastewater treatment process to a biorefinery.
Keywords: Flocculation; Extracellular polymeric substances; Water -- Purification; Sewage -- Purification -- Anaerobic treatment; Integrated algae pond systems (IAPS); Microalgal-bacterial flocs